Critical role of multidimensional biodiversity in contributing to ecosystem sustainability under global change - Ruiyang Zhang; Dashuan Tian; Jinsong Wang; Shuli Niu (Geography and Sustainability, 2023)
The 21st century has seen an acceleration of global change, including climate change, elevated carbon dioxide, nitrogen deposition, and land-use intensification, which poses a significant threat to ecosystem functioning. Nevertheless, studies on the relationship between biodiversity and ecosystem functioning (BEF) have consistently demonstrated that biodiversity enhances ecosystem functioning and its stability, even in variable environmental conditions. These findings potentially indicate the critical role of biodiversity in promoting sustainable provisioning of ecosystem functioning under global change. Our paper provides a comprehensive review of current BEF research and the response of BEF to multiple global change factors. We demonstrate that (1) assessing the effects of biodiversity on ecosystem functioning requires consideration of multiple dimensions of diversity, such as diversity across multiple trophic levels (plants, animals, and microbes), multiple facets (taxonomy, functional traits, and phylogeny), and multiple spatial scales (local, regional, and landscape scales). (2) The interaction of multiple global change factors may lead to a greater reduction in biodiversity and ecosystem functioning than a single global change factor. (3) Multidimensional biodiversity regulates the response of ecosystem functioning to global change factors, indicating that high levels of multidimensional biodiversity can mitigate the negative impacts of global change on ecosystem functioning. Overall, we emphasize that recognizing the importance of multidimensional biodiversity is critical for sustaining ecosystem functioning. Therefore, prioritizing conservation efforts to maintain and enhance all dimensions of biodiversity is essential to address the challenges of future global change.